Effects of myricetin‐3‐O‐α‐rhamnoside (myricitrin) treatment on urinary parameters of Wistar rats. (6th October 2019) - Tenfen, Adrielli; Mariano, Luísa Nathália Bolda; Boeing, Thaise; Cechinel‐Zanchett, Camile Cecconi; da Silva, Luisa Mota; de Andrade, Sérgio Faloni; de Souza, Priscila; Cechinel‐Filho, Valdir
Abstract: Objectives: This study aimed to investigate the diuretic efficacy of myricetin‐3‐O‐α‐rhamnoside (myricitrin), a common naturally occurring plant‐derived flavonoid, obtained from Marlierea eugeniopsoides (D.Legrand & Kausel) D.Legrand leaves in rats. Methods: For that, female Wistar rats were treated by oral route with the different treatments and kept in metaboloic cages for 8‐h or 24‐h experiment. The volume and urinary parameters were measured at the end of the period and compared between groups. Key findings: When orally given to rats and compared to the vehicle‐treated group, myricitrin (0.3 and 1 mg/kg) was able to stimulate rat diuresis, natriuresis and kaliuresis. The combination myricitrin plus hydrochlorothiazide, but not plus furosemide or amiloride, potentiated the urinary volume when compared to the effects of drugs alone. Besides, the 8‐h renal effects of myricitrin were prevented in the presence of a cyclooxygenase inhibitor and a muscarinic receptor antagonist. However, all groups treated with myricitrin showed a significant reduction in Cl − excretion. In addition, a reduction in the urinary excretion of Cl − and HCO 3 - was detected on 24‐h analysis, a result that showed to be associated with an increase of these anions in the blood samples from the myricitrin‐treated group. Despite these alterations, no changes in urinary or blood pH were detected. Conclusions: Taking together, although the results of this study point to the diuretic potential of myricitrin, the reduction in urinary Cl − and HCO 3 - excretion should be considered in future approaches, as well as for therapeutic applicability.